Convergence, plasticity, and tissue residence of regulatory T cell response via TCR repertoire prism - Nakonechnaya, Tatyana O; Moltedo, Bruno; Putintseva, Ekaterina V; Leyn, Sofya; Bolotin, Dmitry A; Britanova, Olga V; Shugay, Mikhail; Chudakov, Dmitriy M (eLife, 2024)
Suppressive function of regulatory T cells (Treg) is dependent on signaling of their antigen receptors triggered by cognate self, dietary, or microbial peptides presented on MHC II. However, it remains largely unknown whether distinct or shared repertoires of Treg TCRs are mobilized in response to different challenges in the same tissue or the same challenge in different tissues. Here we use a fixed TCRβ chain FoxP3-GFP mouse model to analyze conventional (eCD4) and regulatory (eTreg) effector TCRα repertoires in response to six distinct antigenic challenges to the lung and skin. This model shows highly 'digital' repertoire behavior with easy-to-track challenge-specific TCRα CDR3 clusters. For both eCD4 and eTreg subsets, we observe challenge-specific clonal expansions yielding homologous TCRα clusters within and across animals and exposure sites, which are also reflected in the draining lymph nodes but not systemically. Some CDR3 clusters are shared across cancer challenges, suggesting a response to common tumor-associated antigens. For most challenges, eCD4 and eTreg clonal response does not overlap. Such overlap is exclusively observed at the sites of certain tumor challenges, and not systematically, suggesting transient and local tumor-induced eCD4=>eTreg plasticity. This transition includes a dominant tumor-responding eCD4 CDR3 motif, as well as characteristic iNKT TCRα CDR3. In addition, we examine the homeostatic tissue residency of clonal eTreg populations by excluding the site of challenge from our analysis. We demonstrate that distinct CDR3 motifs are characteristic of eTreg cells residing in particular lymphatic tissues, regardless of the challenge. This observation reveals the tissue-resident, antigen-specific clonal Treg populations.
Keywords: buněčné klony; lung challenges; receptory antigenů T-buněk; immunology; inflammation; zvířata; myši; peptidy; TCR repertoire; Mice; Peptides; CD4+ T cells; Receptors, Antigen, T-Cell; Clone Cells; CD4-Positive T-Lymphocytes; CD4-pozitivní T-lymfocyty; regulační T-lymfocyty; antigenic specificity; homing; Animals; T-Lymphocytes, Regulatory; mouse; treg